Glomus tumor of the hyoid bone: a case report and literature review - Shi, Mingrui; Han, Ming; Wang, Jiale; Zhao, Qi; Ren, Chenghao; Li, Huan; Yang, Zihui; Wei, Jianhua; Yang, Xinjie (Frontiers in Oncology, 2025)
Hyoid glomus tumors represent an exceptionally rare clinical entity. This study details a case presentation of a hyoid glomus tumor accompanied by a comprehensive systematic review, aiming to expand the clinical and pathological understanding of these uncommon neoplasms while evaluating therapeutic approaches. CT imaging revealed hyoid bone destruction with features suggestive of a borderline neoplasm. Histopathological examination demonstrated local spindle-shaped cells exhibiting a chicken claw-like morphology, which showed strong immunoreactivity for SMA, calponin, and collagen type IV - findings consistent with classical glomus tumor characteristics. The patient was ultimately diagnosed with a glomus tumor of uncertain malignant potential. Postoperative recovery proceeded favorably, with serial follow-up imaging studies demonstrating no evidence of recurrence or residual disease over several months of surveillance.